Three stage deep network for 3D human pose reconstruction by exploiting spatial and temporal data via its 2D pose - Verma P.; Srivastava R. (My University, 2025)
3D Human Pose Reconstruction (HPR) is a challenging task due to less availability of 3D ground truth data and projection ambiguity. To address these limitations, we propose a three-stage deep network having the workflow of 2D Human Pose Estimation (HPE) followed by 3D HPR; which utilizes the proposed Frame Specific Pose Estimation (FSPE), Multi-Stage Cascaded Feature Connection (MSCFC) and Feature Residual Connection (FRC) Sub-level Strategies. In the first stage, the FSPE concept with the MSCFC strategy has been used for 2D HPE. In the second stage, the basic deep learning concepts like convolution, batch normalization, ReLU, and dropout have been utilized with the FRC Strategy for spatial 3D reconstruction. In the last stage, LSTM deep architecture has been used for temporal refinement. The effectiveness of the technique has been demonstrated on MPII, Human3.6M, and HumanEva-I datasets. From the experiments, it has been observed that the proposed method gives competitive results to the recent state-of-the-art techniques. © 2020 Elsevier Inc.